Singlewide : Chasing the American Dream in a Rural Trailer Park - Salamon, Sonya; MacTavish, Katherine (Ithaca, NY : Cornell University Press, 2017)
In Singlewide, Sonya Salamon and Katherine MacTavish explore the role of the trailer park as a source of affordable housing. America's trailer parks, most in rural places, shelter an estimated 12 million people, and the authors show how these parks serve as a private solution to a pressing public need. Singlewide considers the circumstances of families with school-age children in trailer parks serving whites in Illinois, Hispanics in New Mexico, and African Americans in North Carolina. By looking carefully at the daily lives of families who live side by side in rows of manufactured homes, Salamon and MacTavish draw conclusions about the importance of housing, community, and location in the families' dreams of opportunities and success as signified by eventually owning land and a conventional home. Working-poor rural families who engage with what Salamon and MacTavish call the "mobile home industrial complex" may become caught in an expensive trap starting with their purchase of a mobile home. A family that must site its trailer in a land-lease trailer park struggles to realize any of the anticipated benefits of homeownership. Seeking to break down stereotypes, Salamon and MacTavish reveal the important place that trailer parks hold within the United States national experience. In so doing, they attempt to integrate and normalize a way of life that many see as outside the mainstream, suggesting that families who live in trailer parks, rather than being "trailer trash," culturally resemble the parks' neighbors who live in conventional homes.
Frontmatter -- Contents -- Introduction -- Par t 1. GOING MOBILE IN A RURAL TRAILER PARK -- 1. The Mobile Home Industrial Complex -- 2. Making Ends Meet -- Part 2. CHASING A HOUSING DREAM ACROSS THREE RURAL REGIONS -- 3. The Illinois Park -- 4. The North Carolina Parks -- 5. The New Mexico Parks -- Part 3. IS THE HOUSING DREAM REALIZED BY TRAILER-PARK FAMILIES? -- 6. Youth and Trailer-Park Life -- 7. Reforming the Mobile Home Industrial Complex -- Conclusion -- Acknowledgments -- Appendix A. The Study, Methods, and Sample -- Appendix B. North Carolina and New Mexico Park Population Details -- Notes -- Bibliography -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Housing, Rural -- United States; Mobile home living -- United States; Mobile home parks -- United States; Rural poor -- Housing -- United States; Sociology & Social Science; Urban Studies; 2 -- isacsh